Shedding light on the immunomodulatory properties of galectins: novel regulators of innate and adaptive immune responses - Rabinovich, Gabriel Adrián (2004)
Galectins are a large family of structurally related beta-galactoside-binding proteins that play a pivotal role in the control of cell differentiation, proliferation, activation and apoptosis of many different cell types including immune cells. By crosslinking specific glycoconjugates, different members of the galectin family behave as pro-inflammatory or anti-inflammatory "cytokine-like" mediators, acting at different levels of innate and adaptive immune responses. Here we will review recent advances on the role of galectins in key events of the immune and inflammatory response, such as tolerance induction, cell cycle progression, cell adhesion, chemotaxis, antigen presentation and apoptosis. In particular we will examine the influence of individual members of the galectin family in the physiology of different immune cell types involved in innate and adaptive immune responses. Moreover, we will discuss the importance of these sugar-binding proteins as therapeutic targets in Th1- and Th2-mediated immune disorders, an exciting area for future research.